Aggressive lymphoma after CD19 CAR T-cell therapy: brief report - Kobbe, Guido; Brüggemann, Monika; Baermann, Ben-Niklas; Wiegand, Laura; Trautmann, Heiko; Yousefian, Schayan; Libertini, Silvana; Menssen, Hans D.; Maier, Harald J.; Ulrich, Peter; Gao, Jingbo; Bruch, Peter-Martin; et al. (The New England journal of medicine, 2024)
The development of a fatal, clonal, autonomously proliferating CD4−CD8− chimeric antigen receptor (CAR)+ peripheral T-cell lymphoma (PTCL) occurred 1 month after a patient received treatment with tisagenlecleucel for relapsed primary central nervous system lymphoma. The PTCL had a clonal T-cell receptor rearrangement, which was already detectable in the apheresis product for CAR T-cell manufacturing and 7 months earlier for autologous transplantation. Somatic DNMT3A and TET2 mutations in CD34+ stem cells and their progeny were detected in the PTCL, in the apheresis specimen that was obtained for CAR T-cell production, and in the autotransplant. The PTCL harbored an additional somatic TET2 mutation, which was already detectable in the CAR T-cell apheresis product and the final CAR T-cell product at very low frequencies, providing evidence that clonal hematopoiesis had contributed to lymphomagenesis. Shortly after a patient received CAR T-cell therapy for relapsed CNS lymphoma, an aggressive CAR+ T-cell lymphoma was diagnosed. Subsequent analysis revealed the presence of an abnormal clone in an early apheresis specimen.